2010
DOI: 10.1007/s00401-010-0655-4
|View full text |Cite
|
Sign up to set email alerts
|

The neuropathology of autism: defects of neurogenesis and neuronal migration, and dysplastic changes

Abstract: Autism is characterized by a broad spectrum of clinical manifestations including qualitative impairments in social interactions and communication, and repetitive and stereotyped patterns of behavior. Abnormal acceleration of brain growth in early childhood, signs of slower growth of neurons, and minicolumn developmental abnormalities suggest multiregional alterations. The aim of this study was to detect the patterns of focal qualitative developmental defects and to identify brain regions that are prone to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
406
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 505 publications
(450 citation statements)
references
References 107 publications
27
406
1
3
Order By: Relevance
“…We also attempted to provide some understanding on the nature of this cognitive phenotype by employing a biological motion paradigm as this has a significant correlation with IQ in human ASD (Rutherford and Troje, 2012). A spatial learning paradigm was employed to account for the consequences of the structural deficits observed in the hippocampus of patients with ASD (Wegiel et al, 2010) as these may contribute to the dorsal stream processing deficits associated with this condition. As a measure of construct validity, we evaluated cell adhesion molecule function, specifically neural cell adhesion molecule (NCAM) polysialylation (PSA) state, as this has previously been implicated in the pathogenesis of ASD (Plioplys et al, 1990;Purcell et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We also attempted to provide some understanding on the nature of this cognitive phenotype by employing a biological motion paradigm as this has a significant correlation with IQ in human ASD (Rutherford and Troje, 2012). A spatial learning paradigm was employed to account for the consequences of the structural deficits observed in the hippocampus of patients with ASD (Wegiel et al, 2010) as these may contribute to the dorsal stream processing deficits associated with this condition. As a measure of construct validity, we evaluated cell adhesion molecule function, specifically neural cell adhesion molecule (NCAM) polysialylation (PSA) state, as this has previously been implicated in the pathogenesis of ASD (Plioplys et al, 1990;Purcell et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, black children may have less access to the healthcare system and may therefore be under-diagnosed with ASD [20]. We also surmised that the increasing prevalence of congenital anomalies among white children may contribute to the higher prevalence of ASD in whites, given the possibility of uterine environmental insult [3,11]. In the crude and unadjusted prevalence estimate, black children were less likely to be diagnosed with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological changes in clinical diagnoses have seen drastic rises in ASD incidence, namely from 1 in 150 diagnosed children in 2000 to 1 in 68 diagnosed children in 2010 [9]. Furthermore, several studies have suggested that 5% to 46% of individuals diagnosed with ASD have been observed to develop some degree of epilepsy, with the greatest risk of development appearing in adolescence [10][11][12]. Previous research studying ASD revealed that males were more likely to be diagnosed by a ratio of 4:1, a finding that has been comparable to other neurodevelopmental comorbidities such as dyslexia and attention deficit disorder [1,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations